HEAT LOSS THROUGH EXTERNAL BUILDING ENVELOPES: A CASE STUDY OF THE FACULTY OF ELECTRONICS AND AUTOMATION BUILDING - Umida Akramova (Modern American Journals, 2025)
This study investigates heat loss through the external building envelopes of the Faculty of Electronics and Automation at the university. By analyzing the thermal performance of walls, windows, roofs, and other structural elements, the research identifies the main sources of heat loss that contribute to increased energy consumption. The findings highlight critical areas where insulation improvements can significantly reduce thermal leakage, enhancing energy efficiency and indoor comfort. The study provides practical recommendations for retrofitting and upgrading the building’s envelope to minimize heat loss, which can serve as a model for similar educational facilities aiming to improve sustainability and reduce operational costs.
Keywords: Heat loss, building envelope, thermal insulation, energy efficiency, external walls, windows, roofs, university building, thermal performance, energy conservation, building physics, Faculty of Electronics and Automation.